(untitled) (Latakia University Journal -Basic Sciences Series, 2017)
يهدف هذا البحث إلى تحقيق دارة إلكترونية للتحكم بسوية الماء في خزان. تُظهر الدارة سوية الماء على شكل أرقام عشرية. يمكن التحكم بحجم الماء بحيث إنه إذا انخفضت سوية الماء عن قيمة محددة يتم اختيارها مسبقاً باستخدام مسبر Probeتعمل مضخة المياه. وعندما تصل سوية الماء إلى قيمة أخرى محددة تتوقف المضخة عن العمل. لقد استخدمنا للتحكم بسوية الماء وعاء من الزجاج الشفاف حجمه 15 Lمدرج بتسع سويات للماء. إضافة إلى ذلك ونظرا للتطبيقات الواسعة للوحة الإلكترونية المحققة، يمكننا قياس سرعة دوران محركات DC ضمن مجال واسع ( من 0001 إلى 9999 ) دورة خلال مدة زمنية اختيارية تتراوح من 1 s إلى110 s ، وإظهار هذه السرعة على أربع أدوات إظهار كما تتضمن هذه الدارة قاطعة reset/start لمسح الشاشة وإعادة القياس. قمنا بإجراء هذه الدراسة على عينات من الماء مأخوذة من الصنبور، ومن أجل عدة قيم للبعد بين المساير ولجهد التغذية. وجدنا استجابة سريعة في إظهار السويات وكفاءة عالية في الأداء. وقسنا عدد دورات محرك خاص صغير من اجل عدة قيم للجهد المطبق بين قطبيه خلال 30 s و 60 s ورسمنا العلاقة بين عدد الدورات والجهد المطبق فوجدنا أنها علاقة خطية. The purpose of this research is to design and realization of an electronic circuitthat is able to control the water level in a tank. The circuit shows a tank water level in decimal numbers and controls the volume of water in the tank. So that when the level of water drops below a specific value that is preselected using a probe, the pump water works. When the water level reaches to another limit value, the pump stops working.We used for water level control a container which is made by transparent glass with volume of 15 L. the container is divided in nine levels. In addition to this purpose, because of large applications for realized electronic board, The circuit measures the speed of rotation of DC motorsin a wide range (0001 to 9999) cycles during a chosen period of time that ranges from 1 sec to 110 sec and display the speed of rotation in decimal numbers that appears on four displays. Moreover, the circuit contains a switch reset/start, for display clear and restart of measurement. This study was carried out on samples of tap water, for several values of distance between the probes, and power supply. We found a quick response in showing levels and high efficiency in performance. We measured the number of special motor cycles for several values of the power supply during 30 s and 60 s, and the relation between the number of cycles and applied voltagewas drawingwe found it a linear relation.